Barnyard millet – a potential food and feed crop of future. Issue 2 (22nd January 2015) - Sood, Salej; Khulbe, Rajesh K.; Gupta, Arun K.; Agrawal, Pawan K.; Upadhyaya, Hari D.; Bhatt, Jagdish C.; Prasad, M.
Abstract The two species under genus Echinochloa, E. frumentacea (Indian barnyard millet) and E. esculenta (Japanese barnyard millet), are cultivated for food and fodder by hilly and tribal communities in Asia particularly in India, China and Japan. The crop has wide adaptability and occupies a special place in marginal rainfed areas because of its short life cycle. Although the area under the crop has come down drastically in last 50 years, the crop ability to survive under harsh conditions makes it a better choice during famine years. In the Indian Himalayan region, the crop was traditionally used as a substitute for rice. It has been identified as a suitable choice for climate‐resilient agriculture. High nutrient content and antioxidant effects make it to be considered as a functional food crop. Recently, the demand of the crop has increased due to its highly nutritious grains. Thus, it has the potential to provide both food and nutritional security particularly in hills where nutritional deficiencies are in abundance. Despite enormous potential, the crop has not gained the popularity among masses and is still considered as poor man's food. This work therefore is an attempt to compile the meagre information available on crop history, evolution, crop breeding and present status to make the crop competitive and revamp its cultivation.